Adsorption of Cr (VI) From Polluted Water Using Activated Carbon Prepared From Lagenaria Siceraria - K. Ravindhranath, O. Sreedevi (International Journal of Advanced Science and Technology, 2020)
The action of performing charcoal was from an idea of removal of chromium from polluted water in present days. The absorption characteristics of charcoal come from Lagenaria Siceraria plant stems for removal of chromium from polluted solutions. In surface chemistry the characteristics of absorbed substances were a structure of analysis by FTIR, SEM- EDAX, and XRD. An adsorption experiment has been performed in order to increase initial concentration, PH, in absorbed substances and contact time for removal process. The metal ion has PH dependent to a lesser elongation, ionic strength. A structure of data that is moving continuously was found to follow pseudo- second order of a data structure model. In thermodynamics the scope of an activity such as activation enthalpy, activation entropy, activation Gibbs free energy, and activation energy from an idea and possible of mechanism is also suggested.